Nietzsche: Life and its Becoming conceived as a Woman. Ethico-political Consequences for the Relations between Philosophy and Psychoanalysis - Bornhauser, Niklas; Coloma Arenas, Manuel (Estudios de Filosofía, 2010)
The concept of Life in Nietzsche´s work is a central idea, both in his own thought and in relation to the repercussions it has in contemporary debate. Its multiple meanings exceed the field in which initially it had been set out, inviting to a discussion among the disciplinary frontiers and to interdisciplinary debate. The nietzschean conception of the eternal return is examined from the Lacanian notion of Repetition attempting to clarify the idea of Life as Woman.